2014
DOI: 10.1021/ja503683y
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III) Bound by Hydrosulfide Anion Ligands: NO-Promoted Stabilization of the [FeIII–SH] Motif

Abstract: Spontaneous transformation of the thermally stable [HS](-)-bound {Fe(NO)2}(9) dinitrosyl iron complex (DNIC) [(HS)2Fe(NO)2](-) (1) into [(NO)2Fe(μ-S)]2(2-) (Roussin's red salt (RRS)) along with release of H2S, probed by NBD-SCN (NBD = nitrobenzofurazan), was observed when DNIC 1 was dissolved in water at ambient temperature. The reversible transformation of RRS into DNIC 1 (RRS → DNIC 1) in the presence of H2S was demonstrated. In contrast, the thermally unstable hydrosulfide-containing mononitrosyl iron compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 94 publications
0
28
0
Order By: Relevance
“…Hence, the most reasonable hypothesis is that the product of the reaction is a mononuclear iron-sulfide ([1Fe1S]) species. A number of non-heme mononuclear iron-sulfide inorganic complexes have been reported, thus providing credence to the formation of the same type of species in IscU/ISCU; however, a clear demonstration is still awaited [180][181][182][183][184].…”
Section: Ferredoxin and Iron Mediated Reduction Of Persulfidesmentioning
confidence: 99%
“…Hence, the most reasonable hypothesis is that the product of the reaction is a mononuclear iron-sulfide ([1Fe1S]) species. A number of non-heme mononuclear iron-sulfide inorganic complexes have been reported, thus providing credence to the formation of the same type of species in IscU/ISCU; however, a clear demonstration is still awaited [180][181][182][183][184].…”
Section: Ferredoxin and Iron Mediated Reduction Of Persulfidesmentioning
confidence: 99%
“…Moreover, slow-release H 2 S donors can also generate side-products other than H 2 S, thus complicating precise reactivity studies under controlled conditions. One benefit of using organic solvents to investigate H 2 S/HS − reaction chemistry with bio(in)organic models, such as transition metals [6][7][8][9][10][11][12] or reactive sulfur species, [13][14][15][16][17] is that such constructs enable differentiation of H 2 S reactivity from that of HS − , which is otherwise challenging in protic media. For example, we have previously demonstrated that HS − and H 2 S react differently with Zn and Co phthalocyanine complexes.…”
mentioning
confidence: 99%
“…Similarly, the formation of an RRS [Fe 2 (µ-S) 2 (NO) 4 ] 2− from a DNIC in aqueous solution was observed and the transformation of RRS back to [HS] − bound DNIC was followed by releasing H 2 S. A similar transformation of another compound, [Fe(NO)(SH)(µ-S)] 2 2– , 7 , was also reported (Scheme 5) [80]. The reaction pathway between RRE, [(µ-S(CH 2 ) 2 NH 2 )Fe(NO) 2 ] 2 , 8 , and mixed-thiolate-containing reduced RRE [(µ-SC 6 H 5 )(µ-S(CH 2 ) 2 NH3)Fe 2 (NO) 4 ] − , 9 , via a DNIC was also studied and revealed that it was triggered by cysteamine (Scheme 6) [81].…”
Section: Dinuclear Metal Nitrosyl Complexesmentioning
confidence: 64%